2001
DOI: 10.1074/jbc.m010377200
|View full text |Cite
|
Sign up to set email alerts
|

The Cadherin Cytoplasmic Domain Is Unstructured in the Absence of β-Catenin

Abstract: Background: MGP inhibits tissue calcification, but underlying mechanisms are understudied. Results: In MGP null mice, TG2 ablation prevents calcifying cartilaginous vascular lesions but does not affect elastocalcinosis and elastin fragmentation associated with increased elastase adipsin. Conclusion: MGP acts via two distinct mechanisms. Significance: Our study identifies TG2 and adipsin as potential therapeutic targets in vascular disease linked to MGP deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
177
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(190 citation statements)
references
References 70 publications
8
177
0
1
Order By: Relevance
“…This suggests that both residues must be phosphorylated to compromise E-cadherin adhesion, whereas a recent study indicated phosphorylation of either of these residues compromised Ncadherin adhesion (15). Phosphorylation of ␤-catenin Y489 reduces binding affinity between ␤-catenin and N-cadherin ϳ4-fold whereas phosphorylation of ␤-catenin Y654 reduces binding affinity between ␤-catenin and E-cadherin 6-to 10-fold (9,10,13,15). It is possible that the fourfold reduction in affinity does not itself disrupt E-cadherin binding to ␤-catenin but facilitates the phosphorylation of Y654 that then in combination with phosphorylation of Y489 compromises binding of ␤-catenin and cadherin.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This suggests that both residues must be phosphorylated to compromise E-cadherin adhesion, whereas a recent study indicated phosphorylation of either of these residues compromised Ncadherin adhesion (15). Phosphorylation of ␤-catenin Y489 reduces binding affinity between ␤-catenin and N-cadherin ϳ4-fold whereas phosphorylation of ␤-catenin Y654 reduces binding affinity between ␤-catenin and E-cadherin 6-to 10-fold (9,10,13,15). It is possible that the fourfold reduction in affinity does not itself disrupt E-cadherin binding to ␤-catenin but facilitates the phosphorylation of Y654 that then in combination with phosphorylation of Y489 compromises binding of ␤-catenin and cadherin.…”
Section: Discussionmentioning
confidence: 88%
“…␤-Catenin binds to E-cadherin in the endoplasmic reticulum. In the absence of ␤-catenin binding, the cadherin cytoplasmic domain lacks structure, PEST sites are exposed, and cadherin is rapidly proteolyzed (9,10). Peptides that compete with ␤-catenin for binding to cadherin also interrupt cadherin adhesion (1).…”
mentioning
confidence: 99%
“…A major regulator of cadherin stability is its intracellular binding partner β-catenin (9). In vitro evidence demonstrates that β-catenin/cadherin interactions are dynamically regulated in response to activity (10,11), allowing β-catenin to modify cadherin stability during different forms of synaptic plasticity.…”
mentioning
confidence: 99%
“…When bound to β-catenin, classical cadherins on neighboring cells interact homophilically and, thereby, promote cell-cell adhesion (16). When not bound to β-catenin, classical cadherins are rapidly degraded (17,18). The regulation of classical cadherin function by β-catenin thereby forms the foundation of adherens junctions and is crucial for cell adhesion in all studied bilaterian tissues, including epithelia, neurons, muscles, and bones (3,19).…”
mentioning
confidence: 99%